533 Readmission Rates After Elective Colorectal Cancer Surgery and Its Comparison to National Bowel Cancer Audit in 2019 (NBOCA 2019). (19th August 2022) - Elzaafarany, A; Tawfik, A; Igbekele, T; Day, A
Abstract: Background: The NBOCA 2019 showed an overall 10.8% of patients had an unplanned readmission within 30 days of surgery (for both elective and emergency colonic resection (NBOCA, 2019). Aim: To identify readmissions rates after elective colorectal cancer surgery in our hospital and comparing it to NBOCA 2019. Identifying reasons for readmissions. Method: A single centre, retrospective, observational study was performed between January 2018 – January 2019. We included patients that required readmission to hospital following elective colorectal resections for cancer. Data was collected on patient demographics, primary operation, histopathology, stage, neo-adjuvant chemo/radiotherapy, date, and reason of readmission. Results: Total of 123 patients had elective resection for colorectal cancer.13.8% (17/123) of these patients required readmissions. 70.6% (12/17) readmitted with 30 days of discharge, 29.4% (5/17) beyond 90 days of discharge. 58.8% (10/17) Of the operations that needed readmission were performed laparoscopically, with the most common primary operation resulting in readmission was LAR (52.9%, 9/17). Tumour grades using Dukes classification were A 41.1% (7/17), B 11.8% (2/17), C 35.2% (6/17), D 5.9% (1/17). Neo-adjuvant chemo/radiotherapy was given in 29.4% (5/17) of patients. Overall, the most common reason for admission was small bowel obstruction (SBO) and abdominal/pelvic collection, each by 23.5% (4/17), followed by wound dehiscence (11.8%, 2/17) and SSI (both deep and organ related) (11.8%, 2/17). Conclusions: 13.8% of patients who underwent elective colorectal surgery for cancer were readmitted within 30 days of discharge. Further study is required to investigate more contributing factors to readmission, in order to formulate strategies to help prevent them.